STRATEGI PEMBERDAYAAN PENGENTASAN KEMISKINAN PADA PNPM MANDIRI - Sukidjo Sukidjo (Jurnal Cakrawala Pendidikan, 2009)
AbstractPoverty eradication is one indicator of the success of the development attempts.Poverty is a complex and multidimensional problem. Attempts to eradicatepoverty that have been made so far are not successful because they focus only oneconomic aspects, not on empowerment and involvement of the local people byestablishing local societal institutions. Autonomous PNPM is a program toeradicate poverty that is based on empowerment through learning by (1) creatingan atmosphere accommodating values of universal humanitarianism, societalprinciples and sustainable development (2) strengthening local societal institutions,(3) strengthening potentials through funding, training, and environmentaldevelopment, and (4) protecting the certainty of the programs for the poor.Keywords: poverty, empowerment, autonomous PNPM